Teachers during Covid-19 in Terms of Academic Supervision and Work Life Balance - Wienda Gusta; Zahratul Azizah; Nurhizrah Gistituati; Rusdinal (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of the study was to test the effect of academic supervision and work life balance on teacher performance during Covid-19. This type of research is quantitative with an explanatory research approach. There were 92 teachers of SMK 8 Padang who were selected as samples in the study based on saturated sampling techniques. Research data collected through a questionnaire for academic supervision. The data was collected using questionnaires with a 5-point likert measurement scale. Findings in this study with regression analysis multiple linear showing the results of the analysis that: there is an influence of academic supervision on teacher performance during Covid-19 H1 received; there is a work life balance effect to the performance of teachers during Covid-19 H2 received; and there is an influence of academic supervision and work life balance simultaneously on teacher performance during Covid-19 H3 received.